Human Motion Based On Actor Physique In A Motion Capture Environment: A Case Study - Jong, Sze Joon (2007)
The purpose of this research is to study the detail of motion of various subjects with differences in physical attributes. The research outlines how different physique produces different behavioural patterns based upon mass and proportion. This research considers 'motion' to identify the differences in each subject's physical attributes.